Mechanical responses in the construction process of super-large cross-section tunnel: A case study of Gongbei tunnel. (September 2021) - Zhou, Zhenliang; Zhao, Jinpeng; Tan, Zhongsheng; Zhou, Xianping
Highlights: The structural responses of Gongbei tunnel were monitored. Gongbei tunnel project adopted five-bench fourteen-step excavation method. Removing temporary support was the most dangerous stage in tunnel construction. The stress and deformation of frozen circle are analyzed after thawing. Abstract: This paper presents a case study of super-large cross-section tunnel in Zhuhai, China. The excavation section of Gongbei tunnel is 336.8 m 2 . The construction method of freezing pipe roof and five-bench fourteen-step excavation is expected to be adopted, which is the first case in the world. The tunnel construction risk is great because the stratum which the tunnel passes through is mainly silt and the construction procedure is complex. In addition, the load-transfer mechanisms in tunnelling construction are not clear. In this paper, the field test method and numerical simulation were utilized to study the development and distribution of ground deformation and support deformation during the construction of Gongbei tunnel, and the mechanical responses of tunnel support structure in the tunnelling construction were investigated. The results showed that the ground deformation was uplifted with the excavation of the tunnel due to the freezing and grouting of the surrounding rock. The vault deformation during the excavation process was fluctuating due to Gongbei tunnel was excavated in several steps, which was generally in the state of settlement first and then heave. The peripheral convergence around the tunnel increased first and then tended to be stable with the excavation progress. The removal of temporary support had a slight impact on the convergence around the step C. Due to the existence of the pipe roof and freezing soil, the tunnel supporting stress was small, which ensure the safety of the tunnel structure. Stress results of steel frame of initial support showed that the vault and invert bent to the inside of the tunnel, and the side wall bent to the outside of the tunnel. The bending moment of the secondary lining was larger than that of the initial support due to the ring forming of the secondary lining separately, and the secondary lining might be damaged locally. After the temporary support was removed, the overall stress of the initial support and secondary lining increased slightly. The stress concentration of the secondary lining was relieved after thawing. The interface stress between secondary lining and tertiary lining was large. This case study might severe as a practical reference for similar tunnelling constructions.